Pengaruh Pemberian Antioksidan Vitamin C Dan E Terhadap Konsentrasi Spermatozoa Mencit (Mus Musculus) Yang Dipapar Asap Rokok - Ervina Wati Harahap; Normalina Sandora; Winarto Winarto (Jurnal Ilmu Kedokteran, 2011)
Free radical that are released in cigarette smoke, believed to play an important role in male infertility. The free radicalproduces Reactive Oxygen Species (ROS) that is found increased in male smokers. ROS is one of the free radicalscomponent can be neutralized by vitamin C and E as an antioxidant. This study using those agents to the fifteen minuteshalf piece cigarette to expose mice and count their sperm as the fertilility parameter. The research design used was posttest-only control group with twenty mice were divided into five groups. A group of no smoke exposed was categorizedas a baseline control, the exposed groups were consisted of one group without antioxidant, one group with vitamin Ctreatment, a group of vitamin E treatment and at last the combination of vitamin C and E. All groups were treatedfor fourteen days. The results were analyzed using oneway ANOVA with p<0.05. It is obviously proven that thecombination of vitamin C and vitamin E treatment on the usual dose gave the highest sperm count compared to othergroups.